FREQUENCY DISTRIBUTION OF NON-COMMUNICABLE DISEASES AND INFECTIOUS DISEASES IN POASIA DISTRICT, KENDARI CITY 2023 - Wahyuni, Nur Afiat; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
A disease is an abnormal condition in the body or mind that causes discomfort, abnormality, or dysfunction in a person. Disease classification can be differentiated between non-communicable diseases and infectious diseases. Indonesia is experiencing a double burden, on the one hand, NCDs have increased significantly, but are still faced with infectious diseases that have not yet been resolved. This research aims to describe the frequency distribution of non-communicable and infectious diseases in Poasia District, Kendari City in 2023. This type of research is quantitative descriptive research, which only describes in general the frequency distribution of non-communicable and communicable diseases. This data utilizes secondary data in the form of medical records at the Poasia Health Center. The population in this study was 42,542 people, the subjects of this study were hypertension sufferers, diabetes mellitus sufferers, people suspected of TB and people at risk of HIV infection. The results show that based on the data that has been obtained, non- communicable diseases are hypertension and diabetes mellitus. There were 8,479 people suffering from hypertension, while there were 435 people suffering from Diabetes Mellitus. For infectious diseases, namely TB and HIV, there were 834 people suspected of having TB and 1,279 people at risk of being infected with HIV. The process of disease occurrence is an interaction between the disease agent, humans (host) and the surrounding environment. For infectious diseases, the process of disease occurs due to interactions between: disease agents (living microorganisms), humans and the environment. Meanwhile, for non-communicable diseases, the process of disease occurs due to interactions between disease agents (non-living agents), humans and the environment. Keywords : frequency, non-communicable diseases, communicable diseases